Promoter hypermethylation patterns of P16, DAPK and MGMT in Oral Squamous Cell Carcinoma: A systematic review and meta-analysis - K R Don; Pratibha Ramani; Vijayalakshmi Ramshankar; Herald Justin Sherlin; Priya Premkumar; Anuja Natesan (Wolters Kluwer Medknow Publications, 2014)
Background: Oral squamous cell carcinoma (OSCC) is a common cancer world-wide that is highly lethal due to its recurrence and metastasis. Methylation is a common epigenetic mechanism that leads to gene silencing in tumors and could be a useful biomarker in OSCC. The prevalence of P16, death-associated protein kinase (DAPK) and O 6 -methylguanine-DNA-methyltransferase (MGMT) promoter hypermethylation in OSCC has been evaluated for several years while the results remain controversial. Objective: The aim of this systematic review is to critically analyze and perform a meta-analysis on the various studies in the literature that have reported the promoter hypermethylation of P16, DAPK and MGMT genes in OSCC. Search Strategy: Articles were searched and selected through PubMed. Hand search from the relevant journals was also performed. Articles were reviewed and analyzed. Results: The estimated prevalence of P16 methylation was 43%, DAPK methylation was 39.7% and MGMT methylation was 39.8%. Heterogeneity in methylation prevalences and correlations with the clinical outcomes of the disease prevailed in various studies. Conclusion: We can conclude from our systematic review that a higher prevalence of methylation of P16, DAPK and MGMT occur in OSCC. Further studies are required to substantiate the role of methylation of P16, DAPK and MGMT as a marker in OSCC.